2018
DOI: 10.1002/chem.201705131
|View full text |Cite
|
Sign up to set email alerts
|

Silver(I)‐Mediated Base Pairs in DNA Sequences Containing 7‐Deazaguanine/Cytosine: towards DNA with Entirely Metallated Watson–Crick Base Pairs

Abstract: DNA sequences comprising noncanonical 7-deazaguanine ( G) and canonical cytosine (C) are capable of forming Watson-Crick base pairs via hydrogen bonds as well as silver(I)-mediated base pairs by coordination to central silver(I) ions. Duplexes I and II containing G and C have been synthesized and characterized. The incorporation of silver(I) ions into these duplexes has been studied by means of temperature-dependent UV spectroscopy, circular dichroism, and DFT calculations. The results suggest the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 59 publications
3
22
0
12
Order By: Relevance
“…In addition, the formation of silver‐mediated c 7 A d (7‐deaza‐2′‐deoxyadenosine)‐dT base pairs was reported . Recently, silver‐mediated base pairing of self‐complementary oligonucleotides incorporating a 7‐deaza‐2′‐deoxyguanosine‐dC pair was reported . However, an X‐ray investigation on a related duplex showed that nonhelical structures exist when the sequence motif changes .…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…In addition, the formation of silver‐mediated c 7 A d (7‐deaza‐2′‐deoxyadenosine)‐dT base pairs was reported . Recently, silver‐mediated base pairing of self‐complementary oligonucleotides incorporating a 7‐deaza‐2′‐deoxyguanosine‐dC pair was reported . However, an X‐ray investigation on a related duplex showed that nonhelical structures exist when the sequence motif changes .…”
Section: Resultsmentioning
confidence: 95%
“…However, in the presence of silver ions, the 6‐mer duplex was already too stable to display a complete melting profile (see Figure S5 in the Supporting Information). A similar observation was made on a much longer 14‐mer oligonucleotide duplex with alternating dG‐dC . Consequently, studies were continued on the 4‐mer duplex of 5′‐d(GCGC) (Figure a,b and Figure S6 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations